Guiding principles of hydrogenase catalysis instigated and clarified by protein film electrochemistry - Armstrong, F; Evans, R; Hexter, S; Murphy, B; Roessler, M; Wulff, P (American Chemical Society, 2016)
Protein film electrochemistry (PFE) is providing cutting-edge insight into the chemical principles underpinning biological hydrogen. Attached to an electrode, many enzymes exhibit "reversible" electrocatalytic behavior, meaning that a catalyzed redox reaction appears reversible or quasi-reversible when viewed by cyclic voltammetry. This efficiency is most relevant for enzymes that are inspiring advances in renewable energy, such as hydrogen-activating and CO2-reducing enzymes. Exploiting the rich repertoire of available instrumental methods, PFE experiments yield both a general snapshot and fine detail, all from tiny samples of enzyme. The dynamic electrochemical investigations blaze new trails and add exquisite detail to the information gained from structural and spectroscopic studies. This Account describes recent investigations of hydrogenases carried out in Oxford, including ideas initiated with PFE and followed through with complementary techniques, all contributing to an eventual complete picture of fast and efficient H2 activation without Pt. By immobilization of an enzyme on an electrode, catalytic electron flow and the chemistry controlling it can be addressed at the touch of a button. The buried nature of the active site means that structures that have been determined by crystallography or spectroscopy are likely to be protected, retained, and fully relevant in a PFE experiment. An electrocatalysis model formulated for the PFE of immobilized enzymes predicts interesting behavior and gives insight into why some hydrogenases are H2 producers and others are H2 oxidizers. Immobilization also allows for easy addition and removal of inhibitors along with precise potential control, one interesting outcome being that formaldehyde forms a reversible complex with reduced [FeFe]-hydrogenases, thereby providing insight into the order of electron and proton transfers. Experiments on O2-tolerant [NiFe]-hydrogenases show that O2 behaves like a reversible inhibitor: it is also a substrate, and implicit in the description of some hydrogenases as "H2/O2 oxidoreductases" is the hypothesis that fast and efficient multielectron transfer is a key to O2 tolerance because it promotes complete reduction of O2 to harmless water. Not only is a novel [4Fe-3S] cluster (able to transfer two electrons consecutively) an important component, but connections to additional electron sources (other Fe-S clusters, an electrode, another quaternary structure unit, or the physiological membrane itself) ensure that H2 oxidation can be sustained in the presence of O2, as demonstrated with enzyme fuel cells able to operate on a H2/air mixture. Manipulating the H-H bond in the active site is the simplest proton-coupled electron-transfer reaction to be catalyzed by an enzyme. Unlike small molecular catalysts or the surfaces of materials, metalloenzymes are far better suited to engineering the all-important outer-coordination shell. Hence, recent successful site-directed mutagenesis of the conserved outer-shell "canopy" residues in a [NiFe]-hydrogenase opens up new opportunities for understanding the mechanism of H2 activation beyond the role of the inner coordination shell.